FINANCIAL LITERACY OF CLIENTS: CURRENT ISSUES IN BANKING PRACTICE - Narzieva Guzal Baxtiyorovna (Journals Park Publishing, 2025)
Financial literacy plays a crucial role in ensuring individuals can effectively interact with banking institutions, make informed financial decisions, and manage personal finances. The research is based on qualitative data collected through semi-structured interviews with banking customers and financial experts. The findings indicate that insufficient financial literacy leads to poor financial decisions, including excessive reliance on credit, ineffective savings strategies, and a lack of awareness about financial risks. The study also highlights how banks address these challenges through financial education programs, customer service policies, and digital tools designed to enhance financial awareness. The article discusses the main problems associated with financial illiteracy in banking, examines the factors influencing financial decision-making, and suggests potential solutions for improving financial literacy among banking clients. Strengthening financial literacy is essential for reducing financial risks, increasing customer confidence in banking services, and improving the overall financial health of individuals and households.
Keywords: Savings and investment, digital banking, financial education, consumer financial behavior, banking services accessibility, financial risk management.